1990
DOI: 10.1002/bjs.1800771213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vaginal delivery on the pelvic floor: A 5-year follow-up

Abstract: We have studied the pelvic floor musculature and its innervation in 14 of 24 (58 per cent) multiparous women who had been recruited into a study of the effect of childbirth on the pelvic floor as part of a prospective investigation that began in 1983. These 24 women had all delivered by the vaginal route without forceps assistance. Five of the 14 had developed clinical symptoms of stress incontinence 5 years later; two of them had had a further uncomplicated vaginal delivery during this time. There was manomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
240
3
16

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 557 publications
(273 citation statements)
references
References 14 publications
12
240
3
16
Order By: Relevance
“…Secondly, a significant reduction in maximal squeeze pressure was noted after childbirth, a finding previously described 14,15 , and which seems unlikely to recover with time 16 . However, this reduction did not correlate with the anatomic changes seen, and so may actually represent a diffuse change in sphincter function.…”
Section: Discussionmentioning
confidence: 60%
“…Secondly, a significant reduction in maximal squeeze pressure was noted after childbirth, a finding previously described 14,15 , and which seems unlikely to recover with time 16 . However, this reduction did not correlate with the anatomic changes seen, and so may actually represent a diffuse change in sphincter function.…”
Section: Discussionmentioning
confidence: 60%
“…We speculate that genetic defects in human LOXL1 may lead to clinical syndromes resembling generalized elastolysis affecting skin, lung, large arteries and other organs (e.g., cutis laxa type I; OMIM 219100). Our data also show an unexpected, causal link between elastic fiber homeostasis and pelvic prolapse, a clinical condition strongly correlated with both childbirth and advanced age [21][22][23] . Elastin polymer and soluble elastin-derived peptides also have signaling roles in cell adhesion, migration and proliferation 5,24 .…”
mentioning
confidence: 60%
“…Several authors have demonstrated an association between pelvic floor dysfunctions (especially involving fecal incontinence, sphincter injury and nerve damage) and age and/or mode of delivery (5,26,28) . Anatomical and functional changes of the pelvic floor (anterior compartment) have also been described (12,16,24,25) .…”
Section: Introductionmentioning
confidence: 99%